Desire-state attribution: Benefits of a novel paradigm using the food-sharing behavior of Eurasian jays (Garrulus glandarius). Issue 2 (3rd March 2016) - Ostojić, Ljerka; Cheke, Lucy G.; Shaw, Rachael C.; Legg, Edward W.; Clayton, Nicola S.
ABSTRACT: In recent years, we have investigated the possibility that Eurasian jay food sharing might rely on desire-state attribution. The female's desire for a particular type of food can be decreased by sating her on it (specific satiety) and the food sharing paradigm can be used to test whether the male's sharing pattern reflects the female's current desire. Our previous findings show that the male shares the food that the female currently wants. Here, we consider 3 simpler mechanisms that might explain the male's behavior: behavior reading, lack of self-other differentiation and behavioral rules. We illustrate how we have already addressed these issues and how our food sharing paradigm can be further adapted to answer outstanding questions. The flexibility with which the food sharing paradigm can be applied to rule out alternative mechanisms makes it a useful tool to study desire-state attribution in jays and other species that share food.